The Role of NGO in Promoting Life Long Learning for Person with Visually Impaired and Blindness - Wong, Huey Siew (2012)
The main focus of this paper is to examine how the life long learning take-place through NGO such as Society of the Blind in Malaysia (SBM). Therefore, the aims and objectives of this paper are as follow: 1. To discuss the roles of NGO in the work of life-long learning among the blind and visually impaired community. 2. To share the current practice of NGO serving the blind and visually impaired in life long learning. 3. To identify and report on how the blind and visually impaired can achieved economy empowerment through life long learning.